COMPARATIVE ANALYSIS OF DIFFERENT TYPES OF DENTAL PROSTHESES IN MODERN DENTISTRY - Jalilova Fariza Rasulzhanovna; Tursunboeva Iroda Fakhriddin kizi; Usmanova Khilola Takhirzhanovna (Western European Studies, 2025)
The aim of this work is a comprehensive comparative analysis of the main types of dental prostheses used in modern dentistry: removable, fixed, partially removable, and prostheses on dental implants. A review of materials, design features, clinical effectiveness, durability, biocompatibility, and economic accessibility was conducted. Based on the analysis, the advantages and limitations of each group of prostheses are highlighted. The results obtained can be used by orthopedic dentists to optimize the selection of prosthetic designs and improve the quality of treatment.
Keywords: Dental prostheses; fixed prostheses; removable prostheses